Differentiation of argentine propolis from different species of bees and geographical origins by UV spectroscopy and chemometric analysis - Maldonado, Luis Maria; Marcinkevicius, Karenina; Borelli, Romina Soledad; Gennari, Gerardo Pablo; Salomon, Virginia María; Isla, María Inés; Vera, Nancy Roxana; Borelli, Valeria Soledad (Elsevier, 2019)
Bees collect vegetal resins that they mix with their wax and mechanical impurities to elaborate propolis, whose chemical composition is complex and variable depending on botanical/geographical origin, type of bee, time of year when it was produced and function in the hive. The presence of compounds that absorb UV radiation, such as those of the phenolic type: acids, esters, flavonoids and chalcones, largely responsible for their antioxidant, antimicrobial and anti-inflammatory biological activity has been reported. The objective of the present work was to establish if it was possible to differentiate Argentine propolis using UV spectroscopy and chemometric analysis, in the following cases: (a) Propolis elaborated by three different species of bees (Apis mellifera, Tetragonisca fiebrigi, Scaptotrigona jujuyensis) of the same geographical origin, and (b) Propolis produced by a species of bee (Apis mellifera) of four different geographical origins. UV spectrograms were performed in the 190–420 nm range for all the samples followed by analysis of principal components, hierarchical clusters and linear discriminants. The results showed that Argentine propolis could be differentiated in the two cases studied, and that A. mellifera, T. fiebrigi and S. jujuyensis would not use the same plant species to produce them.